Empirically Estimated Electron Lifetimes in the Earth's Radiation Belts: Van Allen Probe Observations - S. G. Claudepierre; Q. Ma; J. Bortnik; T. P. O'Brien; J. F. Fennell; J. B. Blake (Geophysical Research Letters)
Abstract We use measurements from NASA's Van Allen Probes to calculate the decay time constants for electrons over a wide range of energies (30 keV to 4 MeV) and L values ( L = 1.3–6.0) in the Earth's radiation belts. Using an automated routine to identify flux decay events, we construct a large database of lifetimes for near‐equatorially mirroring electrons over a 5‐year interval. We provide the first accurate estimates of the long decay timescales in the inner zone ( ∼100 days), which are highly resolved in energy and free from proton contamination. In the slot region and outer zone, we compare our lifetime calculations with prior empirical estimates and find good quantitative agreement (lifetimes ∼1–20 days). The comparisons suggest that some prior estimates may overestimate electron lifetimes between L≈ 2.5–4.5 due to instrumental effects and/or background contamination. Previously reported two‐stage decays are explicitly demonstrated to be a consequence of using integral fluxes.